Pemberdayaan Sekolah Lansia Center of Exellent Bina Keluarga Lansia Istiqomah Banjarnegara Melalui Pelatihan Pembibitan Tanaman - Eko Apriliyanto; Arum Asriyanti Suhastyo; Bondan Hary Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This empowerment program for senior citizens at Banjarnegara Polytechnic focuses on improving agricultural skills, particularly plant propagation techniques. Many senior citizens, despite their extensive farming experience, rely on outdated methods that yield suboptimal results, such as poor seedling quality and low germination rates. The program, held on October 3, 2024, at Banjarnegara Polytechnic, aimed to introduce modern agricultural techniques and enhance the participants' knowledge and skills in plant propagation. A total of 25 participants from the CoE BKL Istiqomah attended, with educational backgrounds ranging from elementary school to bachelor's degrees. The event utilized a combination of lectures, practical exercises, and discussions to provide both theoretical knowledge and hands-on experience. The lecture, conducted in Room C.1.2, introduced the basics of plant propagation, while the practical exercises took place at the nursery field of Banjarnegara Polytechnic. The participants gained valuable insights into modern techniques, which they applied directly at the site, ensuring a better understanding of the processes involved. The post-event questionnaire revealed that many participants still viewed farming as a valuable and promising profession, though concerns about the future of farming and its generational continuity were raised. Many participants expressed concerns about passing on farming traditions to the younger generation, indicating a gap between the older and younger generations in agricultural practices. Overall, the program successfully increased the participants' skills in plant propagation and revitalized their enthusiasm for agriculture. Through this activity, senior citizens have been empowered with modern farming knowledge, bridging the gap between traditional and contemporary agricultural practices. The program also opened opportunities for seniors to engage in the modern agricultural sector, fostering a sense of confidence and motivation to continue contributing to the community’s agricultural development.